IMPLEMENTASI PROYEK GITEWS (GERMAN-INDONESIAN TSUNAMI EARLY WARNING SYSTEM) DI KOTA PADANG SEBAGAI UPAYA MEMBANGUN INATEWS (INDONESIAN TSUNAMI EARLY WARNING SYSTEM) - Mustika, Yunes Aplia; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is about a contemporery issue in international relations study which gives description and analyzes about implementations of GITEWS (German-Indonesian Tsunami Early Warning System) project in Padang as efforts to build InaTEWS (Indonesian Tsunami Early Warning System). Padang is area which high in earthquake and tsunami potential. According to the research based on the number of population in coastal area, Padang is the highest in tsunami risk in the world., so Padang needs tsunami early warning system to minimize impacts that will caused by the disaster. This research was developed based on the framework of pluralism perspective that is supported by the theory of international cooperation, as well as the level of analysis using the state as the main actor in international relations. This research used qualitative methods with data collection through observation, interviews, and secondary data collection. GITEWS project in Padang implemented through capacity building with the theme